SOCIALIZATION OF PREVENTION OF THE SPREAD OF COVID-19 AND MARKETING OF MSMES PRODUCTS IN PADASUKA VILLAGE, BAROS DISTRICT, SERANG REGENCY: SOSIALISASI PENCEGAHAN PENYEBARAN COVID-19 DAN PEMASARAN PRODUK UMKM DI DESA PADASUKA KECAMATAN BAROS KABUPATEN SERANG - Nanang Kurniawan; Firda Maryati; Indasari Indasari; Saefullah Aji; Ita Krisdayanti; Khaeruman Khaeruman (Yayasan Education and Social Center, 2021)
Coronavirus is very impactful for people who have lower or medium smoking. Many businesses are experiencing bankruptcy due to unstable sales price conditions, declining consumer demand, revenues than usual before this virus outbreak occurred, and increased production materials. The purpose of this community service activity is to support and strengthen the Covid-19 prevention and prevention program conducted by the Central Government and Local Government, implementing service activities during the Covid-19 pandemic, educating the public about the dangers and ways of preventing Covid-19 through social media, training students to learn with the community to participate and contribute to the prevention and unemployment of Covid-19. Socialization about the dangers of Covid-19 can improve and provide insight and knowledge on the importance of complying with health protocols in daily life to avoid the corona outbreak. With social media, there are many advantages obtained by MSMEs traders. The use of social media can increase revenue, and marketing is much more effective and efficient